Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÐ¾Ð¼Ð±Ð¸Ð½Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÑÑ€ÐµÐ´ Ð½Ð° Ð¿Ð¾Ð²Ñ€ÐµÐ¶Ð´ÐµÐ½Ð¸Ðµ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð², Ð·Ð°Ð¼Ð¾Ñ€Ð¾Ð¶ÐµÐ½Ð½Ñ‹Ñ… Ñ Ñ€Ð°Ð·Ð»Ð¸Ñ‡Ð½Ñ‹Ð¼ Ð³ÐµÐ¼Ð°Ñ‚Ð¾ÐºÑ€Ð¸Ñ‚Ð¾Ð¼ - Ramazanov, V. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Damage of erythrocytes, frozen with low (0.8%) and high (40%) hematocrit values in media with non-penetrative (polyethylene glycol with molecular mass of 1500 and 2000 (PEG-1500, PEG-2000), dextrans) and penetrative (glycerol, dimethylsufoxide, 1,2-propane diol, PEG-400, glucose) cryoprotectants has been studied. Freezing of erythrocytes with high hematocrit in sucrose-saline medium was demonstrated as resulting in higher cell damages if to compare with a low hematocrit. Combining this mentioned medium with non-penetrative cryoprotectant does not eliminate the â€œpackingâ€ effect, while the penetrative ones realise it. The results obtained indicate to the fact, that in order to eliminate the damage, relating to high cell density in freezing medium the combination of sucrose with penetrative cryoprotectants is needed.